2021
DOI: 10.3390/healthcare9080965
|View full text |Cite
|
Sign up to set email alerts
|

Towards Personalized Medicine: Non-Coding RNAs and Endometrial Cancer

Abstract: Endometrial cancer (EC) is the most frequent female cancer associated with excellent prognosis if diagnosed at an early stage. The risk factors on which clinical staging is based are constantly updated and genetic and epigenetic characteristics have recently been emerging as prognostic markers. The evidence shows that non-coding RNAs (ncRNAs) play a fundamental role in various biological processes associated with the pathogenesis of EC and many of them also have a prognosis prediction function, of remarkable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 91 publications
0
64
0
Order By: Relevance
“…Genetic and epigenetic features have been emerging among the prognostic markers of EC [8,68,69]. These could drive clinicians to better select patients for a tailored treatment, in terms of surgical procedures and adjuvant therapies [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and epigenetic features have been emerging among the prognostic markers of EC [8,68,69]. These could drive clinicians to better select patients for a tailored treatment, in terms of surgical procedures and adjuvant therapies [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed that the deficiency in the expression of miRNA correlates with the changes of genes, both on the tissue level as well as circulating blood miRNA, which makes miRNA a potential diagnostic or prognostic biomarker in endometrioid endometrial cancer [ 37 ]. A detailed analysis of the relationship between ncRNA and endometrial cancer has recently been carried out by Piergientili et al [ 38 ] and Cavaliere et al [ 39 ]. Non-coding RNAs (ncRNAs) are RNA molecules that do not have an open reading frame.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data confirm that changes in ncRNA expression can be used as prognostic markers in endometrial cancer. This is possible owing to the development of the next-generation sequencing (NGS) technique [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ncRNAs can have also a diagnostic role. New insights propose a therapeutic marker role, helping in building an “epigenetic profile” [ 82 ]. Actually, various ncRNAs have been individualized as having a role in EC pathogenesis, and for which a functional characterization is available.…”
Section: Discussionmentioning
confidence: 99%